X-rays minibeam radiation therapy at a conventional irradiator: Pilot evaluation in F98-glioma bearing rats and dose calculations in a human phantom. (March 2021) - Sotiropoulos, Marios; Brisebard, Elise; Le Dudal, Marine; Jouvion, Gregory; Juchaux, Marjorie; Crépin, Delphine; Sebrie, Catherine; Jourdain, Laurene; Labiod, Dalila; Lamirault, Charlotte; Pouzoulet, Frederic; Prezado, Yolanda
Highlights: Minibeam radiation therapy at a table top system widens the therapeutic window for high grade gliomas in rats. The first evaluation of a possible treatment plan of X-rays MBRT is reported. An upper dose threshold for normal tissue toxicity in MBRT could be established. Abstract: Minibeam radiation therapy (MBRT) is a type of spatial fractionated radiotherapy that uses submillimetric beams. This work reports on a pilot study on normal tissue response and the increase of the lifespan of glioma-bearing rats when irradiated with a tabletop x-ray system. Our results show a significant widening of the therapeutic window for brain tumours treated with MBRT: an important proportion of long-term survivals (60%) coupled with a significant reduction of toxicity when compared with conventional (broad beam) irradiations. In addition, the clinical translation of the minibeam treatment at a conventional irradiator is evaluated through a possible human head treatment plan.